Proposta de implantação do sistema de compras públicas sustentáveis em uma instituição federal de ensino superior - Bavaresco, Alessandra Daniela (2013)
The sustainable public procurement represents a form of integration of environmental and social criteria in order to decrease the impacts that may harm people's health and the environment. This study aimed to present a proposal for implementation of sustainable procurement in a Federal Institution of Higher Education. For this, qualitative-quantitative research, with prescriptive character presents a study case at the Federal University of Santa Maria. Initially, the placement of external control organs was identified between 2010 and 2012, through documentary analysis. Then technique was applied to the questionnaire in order to show the scenario of Brazilian Federal Institution of Higher Education, 2010-2011 period, with respect to the inclusion of sustainable procedures in their bids. The politics procurement of the institution, analyzed between 2010-2012, took through interviews and procedures analysis. The results indicate that the recommendations proposed by Court of Auditors of the Union promoted joint actions of ministries for sustainable development within the Union. Moreover, identified that the decisions of that Court has been guiding institutions to adopt practices that enable adoption of sustainable environmental criteria in bids. Even partially, it can be seen that the inclusion of sustainable questions on procurement of Federal Institution of Higher Education presents the positive developments in the period under review. It was observed that the unit studied already taking actions relating to purchases of recyclable and reusable materials, energy efficiency and reduction of water consumption, which reveals, although partially, adopting a sustainable approach in their procurement processes. Given the diagnoses presented, it was possible to propose a procurement plan in order to direct the procurement and contracting of the institution from the perspective of sustainable development.